Comparison of the relative stability of pharmaceutical cocrystals consisting of paracetamol and dicarboxylic acids. (3rd April 2018) - Suzuki, Naoto; Kawahata, Masatoshi; Yamaguchi, Kentaro; Suzuki, Toyofumi; Tomono, Kazuo; Fukami, Toshiro
Abstract: Objective: The aim of this study is to evaluate the relative stability of pharmaceutical cocrystals consisting of paracetamol (APAP) and oxalic acid (OXA) or maleic acid (MLA). Significance: These observations of cocrystal stability under various conditions are useful coformer criteria when cocrystals are selected as the active pharmaceutical ingredient in drug development. Method: The relative stability was determined from the preferentially formed cocrystals under various conditions. Result: Cocrystal of APAP–OXA was more stable than that of APAP–MLA in a ternary cogrinding system and possessed thermodynamical stability. On the other hand, when grinding with moisture or maintaining at high temperatures and relative humidity conditions, APAP–MLA was more stable, and OXA converted to OXA dihydrate. In the slurry method, APAP–OXA was more stable in aprotic solvents because the APAP–OXA with low-solubility product precipitated. Conclusions: The relative stability order was affected by preparing conditions of presence of moisture. This order might attribute to the small difference of crystal structure in the extension of the hydrogen bond network.